Sue Harrisonの先史時代小説の特質 - 河島, 弘美; カワシマ, ヒロミ; Kawashima, Hiromi (東洋学園大学, 1996)
Sue Harrison’s debut novel, Mother Earth Father Sky, was published in 1990 as the first of a trilogy, and well-received. The novel’s heroine is an Aleut girl named Chagak who becomes the only survivor of the massacre of her village. On her way to her grandfather’s tribe, she meets Shuganan, a wise, old man who carves ivory very well. He helps Chagak afterwards till she finds a new relationship with Kayugh and his people. Several reviewers have compared Mother Earth Father Sky with Jean Auel’s Clan of the Cave Bear and its sequels, because they are all set in prehistoric age. So-called prehistoric fiction is establishing itself as a new genre in the United States, being represented by the works of Harrison and Auel. Though they try to re-create ancient worlds in each way, Harrison has been superior to Auel so far in skillful storytelling and the detailed description of characters and their life. Harrison’s sympathy with the Aleut culture nine thousand years ago makes the story very appealing. Characters well-drawn with a rich inner life are original and credible. Sue Harrison’s novels have proved that prehistoric fiction can be very successful among the readers today who love exciting stories and also find the simple life-style of ancient people both interesting and instructive. departmental bulletin paper